COENOLOGICAL STATUS OF THE IRIS MEADOWS IN HUNGARY - SALAMON-ALBERT, E.; LORINCZ, P. (Annali di Botanica, 2010)
Species composition and vegetation structure by association and local diagnostic, constant and dominant species of Iridetum sibiricae was analysed from Hungary adjusting to the evaluation of European vegetation. Classification, ordination and statistical analyses was carried out to characterize and make distinction to some other wet meadow vegetation types. In the association habitat and management dependent subunits were formed.